Does Higher Openness Cause More Real Exchange Rate Volatility? - Calderon, Cesar (Elsevier, 2018)
Our study investigates the factors driving RER volatility and the properties of both trade and financial openness to stabilize RERs. Therefore, this paper guides us to formulate better economic policies to lower RER variability. Our goal is to test whether the extent and composition of international trade and financial integration would smooth the impact of shocks to the RER for 82 countries from 1974 to 2013. Our findings support existing theoretical models (Obstfeld and Rogoff, 1995; Hau, 2000). They confirm empirically that the composition of trade and financial openness matters for RER stabilization. We show that trade in manufacturing helps reduce RER volatility while non-manufacturing trade may contribute to higher RER volatility. Financial openness mitigates (amplifies) RER volatility in a country with higher (lower) share of foreign equity vis-à-vis foreign debt liabilities. A greater share of equity in external liabilities can improve the country's resilience to external shocks (Rogoff, 1999). Consequently, policies to lower RER volatility should account for a) the composition of financial openness as measured by the type of capital flows (i.e. equity vs. loan-related) accumulated in the domestic economy and b) the role of the structure of trade (i.e. manufacturing vs. non-manufacturing) in the transmission process of shocks to the RER. Our evidence relates to findings of mitigating effects on sudden stops of trade openness (Cavallo and Frankel, 2008), and equity- rather than debt-related financial openness (Levchenko and Mauro, 2007; Calderón and Kubota, 2013).